2022
DOI: 10.3389/fpubh.2022.864272
|View full text |Cite
|
Sign up to set email alerts
|

Development Work in Swedish Eldercare: Resources for Trustworthy, Integrated Managerial Work During the COVID-19 Pandemic

Abstract: The extensive needs for developments of eldercare addressing working conditions, care quality, influence, and safety was highlighted during the pandemic. This mixed-method study contribute with knowledge about capability-strengthening development work and its importance for trustworthy managerial work, before and during the COVID-19 pandemic. Questionnaire data and narratives from first-line managers immediately before (n = 284) and 16 months into the pandemic (n = 189), structured interviews with development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Since then, many municipalities and counties in Scandinavian countries have begun their journey towards trust-based management. Reviews conclude that many of the interventions are mainly directed at lower-level managers (Dellve, 2023;Dellve & Williamsson, 2022). However, case studies have shown that successful implementation needs congruence in discourse and actions between strategic and lower-level management (Astvik et al, 2020;Bentzen, 2019;Torfing et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many municipalities and counties in Scandinavian countries have begun their journey towards trust-based management. Reviews conclude that many of the interventions are mainly directed at lower-level managers (Dellve, 2023;Dellve & Williamsson, 2022). However, case studies have shown that successful implementation needs congruence in discourse and actions between strategic and lower-level management (Astvik et al, 2020;Bentzen, 2019;Torfing et al, 2021).…”
Section: Introductionmentioning
confidence: 99%